2013
DOI: 10.1007/s11255-013-0438-7
|View full text |Cite
|
Sign up to set email alerts
|

Is residual renal function and better phosphate control in peritoneal dialysis an answer for the lower prevalence of valve calcification compared to hemodialysis patients?

Abstract: Our study shows that the residual renal function in PD patients contributes significantly to the maintenance of phosphate balance and may explain the lower prevalence of valve calcification in PD patients compared with HD patients in the period up to first 3 years under renal replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 43 publications
4
26
0
Order By: Relevance
“…A previous study confirmed that residual renal function (RRF) is one of the key determinants of P control in PD patients. In the present study, we found that the PD group had higher RRF, which led to lower P and Ca×P product levels compared to HD patients [19]. This finding may be explained by the lower salivary P level in PD group than that in the HD group.…”
Section: Discussionsupporting
confidence: 46%
“…A previous study confirmed that residual renal function (RRF) is one of the key determinants of P control in PD patients. In the present study, we found that the PD group had higher RRF, which led to lower P and Ca×P product levels compared to HD patients [19]. This finding may be explained by the lower salivary P level in PD group than that in the HD group.…”
Section: Discussionsupporting
confidence: 46%
“…An American cross-sectional study found more frequent CAC in pediatric patients on hemodialysis (9/21 patients) than on peritoneal dialysis (2/17 patients) [11]. An Albanian cross-sectional study found more frequent cardiac valve calcification in adult patients on hemodialysis (24/34 patients) than on peritoneal dialysis (10/30 patients) [12]. A Korean cross-sectional study did not find a significant difference in CAC score between patients on hemodialysis (n = 31, median score 30) and those on peritoneal dialysis (n = 15, median score 16) [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, there have never been randomized studies on this subject, as randomization to dialysis modality is generally refused by patients [9]. Moreover, patients on peritoneal dialysis are typically younger and healthier due to the prerequisites of treatment at home [10], which has hampered previous observational research that did not attempt to statistically adjust for this [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, similar results are presented Rroji and associates. 23 Furthermore, it is worth mentioning that there was no significant difference of values serum calcium and intact parathyroid hormone in the patients with and without CVCs at the end of the monitoring period.…”
Section: Discussionmentioning
confidence: 82%